Information and Communication Technology in Technical Education - Oviawe, Jane Itohan (Advances in Social Sciences Research Journal, 2016)
Technical education is sine qua non to the economic and industrial growth and development of any nation, Nigeria inclusive. Its primary objective is to provide its recipients functional and employable skills required in the world of work. Today’s world of work is experiencing innovations as a result of technological advancement through the emergence of information and communication technologies (ICTs). These changes brought by ICTs have cut across all spheres of life including social interaction, business practices, healthcare, political engagement, media, education and knowledge dissemination. It is in light of the above that this paper examined. To tackle the issue of this innovation, this paper proposes the integration of ICT into technical education programmes in Nigeria. For technical education to take its rightful place in the era of information age, ICT should be enshrined effectively in the technical education curriculum. Constraints hindering the effective integration of ICT in technical education programmes were highlighted. The paper concluded that ICT skills are the key things that will enable technical education graduates face the challenges of the 21st century workplace. It was recommended that government should provide enough funds to equip schools with ICT tools, equipment and facilities for better delivery of instruction.